PEMILIHAN BIBIT TERNAK SAPI POTONG MELALUI KOMBINASI METODE AHP DAN METODE MFEP - Afrisawati Afrisawati; Irianto Irianto (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2019)
Beef is a livestock product that has economic value. The high demand for meat requires farmers to cultivate cows by supplying cattle to meet consumer needs. In terms of selecting beef cattle seeds, independent breeders still do traditionally. During this time farmers still use the trial and error method in choosing the best type of cow even just concerned with the price factor. This will obviously affect the quality of cattle which results in expensive maintenance costs, less than optimal production yields and even death of cows. The purpose of this study was to conduct a study of the application of technology in the selection of the best beef cattle to increase livestock yield, especially for local independent breeders. The technology used is a combination of the Analytical Hierarchy Process (AHP) method and the Multy Factor Evaluation Process (MFEP) Method. Through a combination of methods, researchers analyzed each criterion and alternative related to the selection of the best beef cattle. AHP method was chosen because it has the ability to analyze more consistent criteria. While the selection of the MFEP method is due to having the ability to analyze alternatives based on existing criteria in a simple and accurate way. The results of the AHP and MFEP analysis method are AHP analysis to assist in determining the priority factors of beef cattle seedlings and applied to the MFEP method which produces the highest alternative A6 with a value of 0.508. This research is expected to become a new foundation for farmers in knowing the criteria and alternatives in determining the best type of beef cattle.